Eye movements and ERP biomarkers for face processing problems in avoidant attachment-style individuals - Gu, Simeng; Jiang, Yao; Liu, Mei; Li, Yumeng; Liang, Yuan; Feng, Rou; Xu, Minghong; Wang, Fushun; Huang, Jason H. (Frontiers in Behavioral Neuroscience, 2023)
Background: Avoidant attachment poses a severe risk in intimate relationships and offspring. However, there are few studies on the facial processing characteristics and impairments of avoidant individuals based on basic emotion theory. Therefore, this study investigated the issues in emotional processing and deactivating strategies in individuals with avoidant attachment. Methods: Avoidant and secure individuals were recruited to participate in an eye-tracking experiment and a two-choice oddball task in which they needed to distinguish facial expressions exhibiting basic emotions (sadness, anger, fear, disgust, and neutral). The eye fixation duration towards various parts of the face, including the eyes, nose and mouth, were measured, and three event-related potentials (ERP) components P100, N170, and P300 were monitored. Results: Avoidant individuals could not process facial expressions as easily as secure individuals. The avoidant individuals focused less on the eyes of the angry faces when compared to secure individuals. They also exhibited a more positive P100 component and a less negative N170 component in processing faces and a larger amplitude of P300 component than secure individuals while processing emotional expressions. Conclusion: Avoidant individuals use deactivating strategies and exhibit specific characteristics at different stages, which are of great significance in social interaction.